Letramento e identidades sociais em um município multilíngue no Paraná - Semechechem, Jakeline Aparecida (2010)
This paper reports a qualitative-interpretive ethnographic research method which investigated what kind of identities would be relevant in talk-interaction during literacy events, at Prudente de Moraes School, inside a multilingual contextualized town, in Southeast of Paraná State. To support this work, on 3th level of Secondary Education Class, 18 hours of lectures were recorded on audio and video and was made transcription of recorded material. Questionnaires and interviews were filled by those students and teachers. In order to improve the comprehension besides situated talk-in-interaction, researcher's field work notes were incorporated to this work, participant observation, as well interviews and questionnaires were similarly applied to the community. These methods were all of them based on Data Collection methods of Ethnographic Methodology skills. Theoretical background that based the data analysis was: New Literacy Studies (NLS), with its socio-cultural approach, Ethnomethodological Conversation Analysis with their Methodological-Analytic Procedures (ECA) and Interactional Sociolinguistics (IS) as well Ethnomethodological Concepts of Identity and also Membership Categorization Analysis, (MCA). About results, talk-interaction data analysis showed on sequentiality talk-interaction, beyond the membership categorizations as teacher, as student and other kind of social identities, revealed other identities roles such as ethnic identity, ruralist identity and religious identity. Some of those identity roles were assumed such as the Germanic identity, Ukrainian identity and Catholic identity. By the other side, some of identity roles were rejected likewise the evangelical religious identity and the ruralist identity. The ruralist identity had been denied by some members of it, but it was assumed by these members, just when the teacher class, assumed herself as a member of this ruralist identity. About Literacy issues data indicated clearly that these social identities interfere with those members who negotiate them and with the literacy events configuration too. About community, school database showed perceptible identity process stuff and conflicts which have been existing in this town and indicates the presence of a "minoritarizated" multilingual context where relationships are not homogeneous but also there are identities which are more legitimated than the others, depending on local values and the negotiation among different ethnical, social and religious groups. In addition the community has been in transition at the moment. Population rearrangement approaches, new religions and orientation for an urban way of living inside a predominant rural community corroborate the identity conflicts in this town.